AN INTEGRATED APPROACH TO THE DIAGNOSIS AND TREATMENT OF ADHESIVE DISEASE IN CHILDREN (Herald of the National Children's Medical Center, 2024)
Adhesive disease is characterized by the formation of splices (cords and adhesions) from the connective tissue between the organs of the abdominal cavity. Adhesions disrupt the functioning of internal organs, cause pain and discomfort, and can also cause complications: chronic pain syndrome, intestinal obstruction, and even infertility in girls in the future. In most cases, adhesions are formed due to an inflammatory process in the abdominal cavity, or after surgical treatment.